FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DALAM LAPORAN TAHUNAN PERUSAHAAN - Nugraha, Septian Adi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to analyze some factors which influence the disclosure of Corporate Social Responsibility (CSR) in the annual report of manufacturing company consumption of goods industry sector. Independent variables which are used in this research are the size of company, the size of board of commissioners, foreign shareholding and the size of audit committee. This research has found some proves that the size of a company has significant influence to the disclosure of CSR, the size of Board of Commissioners has no significant influence to the disclosure of CSR, Foreign Shareholding has no significant influence to the disclosure of CSR, and the size of audit committee has significant influence to the disclosure of CSR. Keywords: Corporate Social Responsibility, the size of Company, the size of Board of Commissioners, Foreign Shareholding, the size of Audit Committee.